MEASUREMENT OF LIQUID VISCOSITY USING LONG EXPOSURE IMAGE ANALIZE - HAJI AMAHORU (NIM : 90214018), ABD.
Physics is the science that studies the phenomena or natural phenomena which observation is one very important aspect. Observations were made to study the physical phenomena and, if necessary, observations can be made using the appropriate device and easily accessible as well as sophisticated. In this study developed a sighting device on a straight motion viscometer tube and liquid viscosity measurement method falling ball (falling ball) using techniques Long Exposure. The viscosity of a fluid is the inhibition caused by friction between the molecules, which are able to withstand fluid flow. While Long Exposure is a technique of shooting on the camera is capable of recording all traces of objects moving at a certain time that can not be captured with the naked eye. The ball fell to the method (falling ball), which became the main part is how to determine the value of the maximum speed when the ball is moving in a fluid. In the experiments conducted, lightmeter be a solid ball with varying sizes coated with phosphorus paint removed from the surface of the liquid (glycerin and honey) on the tube will move along the tube. The device has a camera feature long exposure placed in front of a perforated disk that serves as a counter (chopper) are slit for the camera to capture the trajectory of the ball and turn it into discrete traces. With processing techniques and digital image analysis simple, found traces of ball that shows the value of the position in each interval, so the speed of the ball that moves can be observed and identified both when they move accelerated (Motion Straight Turned Irregular) or after moving with constant velocity (Straight Motion Regularity). Further analysis of the liquid viscosity and obtain best value is 0.7885 Pa.s viscosity with error 6:55% for glycerin, and the best value for the viscosity of honey 3.9162 with precision reached 99.98%. Also obtained viscosity values of mixing the two substances (water and honey) with mixing varying volume. It can be concluded that these devices can be used to observe the phenomenon of Straight Motion Regularity and Motion Straight Turned Irregular on the tube viscosity, determines the value of the viscosity of a liquid, and analyzing the viscosity of the mixing of two liquids with good accuracy and precision was very good.